Surface Planarization‐Epitaxial Growth Enables Uniform 2D/3D Heterojunctions for Efficient and Stable Perovskite Solar Modules - Dongxu Lin; Jun Fang; Sibo Li; Zhenye Zhan; Huan Li; Xin Wang; Guanshui Xie; Daozeng Wang; Nuanshan Huang; Haichen Peng; Weiguang Xie; Luis K. Ono; et al. (Advanced Science)
Abstract Two‐dimensional/three‐dimensional (2D/3D) halide perovskite heterojunctions are widely used to improve the efficiency and stability of perovskite solar cells. However, interfacial defects between the 2D and 3D perovskites and the poor coverage of the 2D capping layer still hinder long‐term stability and homogeneous charge extraction. Herein, a surface planarization strategy on 3D perovskite is developed that enables an epitaxial growth of uniform 2D/3D perovskite heterojunction via a vapor‐assisted process. The homogeneous charge extraction and suppression of interfacial nonradiative recombination is achieved by forming a uniform 2D/3D interface. As a result, a stabilized power output efficiency of 25.97% is achieved by using a 3D perovskite composition with a bandgap of 1.55 eV. To demonstrate the universality of the strategy applied for different perovskites, the champion device based on a 1.57 eV bandgap 3D perovskite results in an efficiency of 25.31% with a record fill factor of 87.6%. Additionally, perovskite solar modules achieve a designated area (24.04 cm2) certified efficiency of 20.75% with a high fill factor of 80.0%. Importantly, the encapsulated uniform 2D/3D modules retain 96.9% of the initial efficiency after 1246 h operational tracking under 65 °C (ISOS‐L‐3 protocol) and 91.1% after 862 h under the ISOS‐O‐1 protocol.